SYRINGIC ACID AND PHENAZINE PRODUCED BY AN ENDOPHYTIC Pseudomonas aeruginosa STRAIN G-111-0317 AND THEIR ACTIVITIES AGAINST Ganoderma boninense - Rupaedah, Bedah; Nurlaila, Nurlaila; Lutfia, Anisa (BRIN - Badan Riset dan Inovasi Nasional, 2023)
Syringic acid and phenazine possess antibiotic and antifungal properties, and have demonstrated effectiveness in inhibiting the colonization of Ganoderma boninense on oil palm plants. Some bacteria, including Pseudomonas aeruginosa strain G-111-0317, are capable of producing syringic acid and phenazine. In this study, the culture extract of this bacterial strain was obtained from healthy oil palm plants growing in G. boninense-infected areas at Oil Plant Plantation Pematang Siantar, North Sumatra. The strain was cultured on Nutrient Broth (NB) medium, and the resulting culture filtrate was extracted using ethyl acetate (EtOAc) and concentrated under vacuum. The putative compounds were identified by LC-MS, employing syringic acid and phenazine as reference standards. Antifungal activity against G. boninense in vitro was observed in the EtOAc extract obtained after 8 hours and 24 hours of fermentation, with the 8-hour extract demonstrating the highest activity. These compounds hold promising potential as active agents in inhibiting basal stem rot disease in oil palm plants.